THE HOLISTIC PERFORMANCE OF AN ENVIRONMENTAL APPROACH: SENEDD CASE STUDY - Fenty Ratna Indarti (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2020)
As the awareness of climate change increased, more sustainable designs are available for not only domestic building but also non domestic building. Focusing on integration with the environmental condition of the site, Senedd (The National Assembly of Wales) is designed to embrace nurture the potential of its site. The utilisation of environmental approach on management, energy, water, materials, pollution, health and wellbeing, waste and innovation leads to an excellent BREEAM rating for the building. This paper aims to study the integration of each environmental consideration utilised in the building. The investigation illustrates how the building perform in three aspects: daylight, natural ventilation and thermal comfort. The study represents that a balance of environmental design approach is demonstrated in the building to achieve its best performance by maximising passive strategies instead of active system.